2020
DOI: 10.2298/tsci190905094z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of climatic conditions on fire risk in Djerdap National Park (Serbia): A case study of September 2011

Abstract: The Djerdap National Park in Serbia is vulnerable to fires. The variability of a fire in the Djerdap National Park is studied depending on the impact of climatic conditions. The influence was investigated on a yearly, monthly, and daily basis using data recorded at the meteorological station Veliko Gradiste. Data were analyzed for two periods: 1961-1990 and 1991-2017, and for the year of 2011. Special attention is devoted to the conditions for the emergence of the largest forest fire in the Djerdap National Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…For the analysis of climatic elements, the data (1990-2021) from the meteorological station Veliko Gradište [43] was used, located at an altitude of 80 m above sea level and 17 km from Golubac. Golubac and its surroundings are characterized by a moderate-continental climate with significant regional climate differences compared to Zlatibor [48]. The Golubac Fortress is a medieval fortress in the northeastern part of Serbia, on the right bank of the Danube.…”
Section: Study Areamentioning
confidence: 99%
“…For the analysis of climatic elements, the data (1990-2021) from the meteorological station Veliko Gradište [43] was used, located at an altitude of 80 m above sea level and 17 km from Golubac. Golubac and its surroundings are characterized by a moderate-continental climate with significant regional climate differences compared to Zlatibor [48]. The Golubac Fortress is a medieval fortress in the northeastern part of Serbia, on the right bank of the Danube.…”
Section: Study Areamentioning
confidence: 99%
“…As droughts have been observed to increase in frequency, intensity and duration in Serbia, more frequent wildfires are expected, especially in south-eastern and eastern Serbia. The Modified Angstrom and Nesterov indices can be used to assess the risk of fire, including Serbia (Ratknić et al, 2019;Živanović and Tošić, 2020). Wildfires affect sustainable forest management and incur a substantial loss to forestry.…”
Section: Introductionmentioning
confidence: 99%
“…Forest fires occur in Serbia almost every year and are a limiting factor in the sustainable development of forestry [27]. Many studies [4,19,20,26,28,29,30,31] have indicated that there is a correlation between the occurrence of forest fires in Serbia and climate conditions. The distribution of the fire-affected areas and the dynamics of fire outbreaks can be correlated with the climatic characteristics of certain areas [25].…”
Section: Introductionmentioning
confidence: 99%